2012
DOI: 10.1021/jp3076063
|View full text |Cite
|
Sign up to set email alerts
|

White Light and Heat Sensitivity in a Pyridine-Based Polymer Blend

Abstract: Sensing from the ultraviolet to the infrared is important for a number of scientific and industrial applications. Poly(4-vinyl pyridine) swollen in liquid pyridine functions as a photoconductive gel sensitive to irradiation in the ultraviolet. By blending poly(4-vinyl pyridine) with poly(4-vinyl pyridineco-butyl methacrylate), we have now succeeded in expanding the range of wavelength sensitivity of the gel to cover the whole visible spectrum. Furthermore, addition of a small amount of 4-hydroxypyridine to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…3 When P4VP is dissolved in dry liquid pyridine and allowed to gel, unique opto-and thermo-electronic behavior is observed. These properties have been studied extensively during the last few years, both experimentally [4][5][6] and by using computational methods. 7 Previously it was suggested that the unique optical properties of the P4VP gel are related to the transfer of a methyne proton to a side chain pyridine nitrogen with the formation of a pyridinium ion NH + .…”
mentioning
confidence: 99%
“…3 When P4VP is dissolved in dry liquid pyridine and allowed to gel, unique opto-and thermo-electronic behavior is observed. These properties have been studied extensively during the last few years, both experimentally [4][5][6] and by using computational methods. 7 Previously it was suggested that the unique optical properties of the P4VP gel are related to the transfer of a methyne proton to a side chain pyridine nitrogen with the formation of a pyridinium ion NH + .…”
mentioning
confidence: 99%
“…We demonstrate this concept on poly(4vinylpyridine) (PVPy)−pyridine (Py) smart gel optoelectronic devices. 41 This material proved to be useful in optoelectronics 53 and memory devices. 54 A PVPy−Py-derived device was fabricated from the smart gel as a photoactive material and assembled with modified ITO substrates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As predicted, the same trend of WF tuning was obtained for both ITO and Si/SiO 2 modification. Moreover, as a proof of concept, the modified ITO substrates were used in organic electronic devices. The ability to control the WF of ITO improved the I – V performance of the modified ITO electrode-based device compared to the device built with bare ITO electrodes, thus proving the major role of monolayer modification on bulk and device features.…”
Section: Introductionmentioning
confidence: 99%
“…Thoroughly dried P4VP dissolved in dry pyridine, taken in the equimolar ratio to the pyridine repeat units of the polymer, produces stable solid photo-and electrosensitive gels P4VP/Py [14]. The physical aggregation of polymer chains was shown to occur due to the presence of the hydrogen bond network, and these gels exhibit not only high ionic conductivity (polyelectrolyte behavior), but also enhanced photoinduced electron mobility [15,16]. The P4VP/Py gel was shown to exhibit unusual emission with the maxima at 477, 527, and 584 nm, explained by photoinduced proton transfer [17], which resembled the emission from the irradiated pyridine [12].…”
Section: Introductionmentioning
confidence: 99%